Design Alternatives Selection for Cost and Time Efficiency Using Value Engineering Method: Case Study of Ramp 5 Wringinanom Junction Krian – Gresik Toll Road - Apriliani, Rizki Astri; Syakurohin, Martinur Mubdi; Santosa, Rudy; Hastono, K. Budi; Yuliastuti, Dayat Indri (Journal of Advanced Industrial Technology and Application, 2024)
The Surabaya Raya toll network encompasses two critical sections connected by the Wringinanom Junction and links the Trans Java Toll Road Surabaya – Mojokerto at KM 723 with the Krian – Gresik Toll Road at KM 3+300 in Wringinanom District, Gresik Regency. This junction includes four ramps to facilitate connectivity, with Ramp 5 intersecting the Surabaya – Mojokerto Toll Road Rest Area at KM 725A and serves traffic from Gresik to Surabaya. This intersection necessitates a design adjustment to enhance traffic flow and safety. This study aims to analyse feasible design alternatives for Ramp 5 by comparing their time and cost efficiency, examining potential construction delays, and determining the most efficient option. The value engineering process comprised information gathering, creative ideation, analysis using the paired comparison method, and recommendation. In the creative phase, three design alternatives were proposed. The paired comparison analysis revealed that the third design alternative that features the tunnel construction under the rest area, is the most efficient, with an estimated cost of IDR 126,236,641,897.46, a duration of 98 days, and a more practical construction aspect. Consequently, the third design alternative was recommended for implementation in this study.